Life cycle assessment : a metric for the circular economy - Borrion, Aiduan; Black, Mairi J.; Mwabonje, Onesmus (Royal Society of Chemistry, 2021)
This book provides a practical guide for those who wish to use life cycle assessment as a research tool or to inform policy, process, and product improvement.